Studies on Apparent Strain Using FBG Strain Sensors for Different Structural Materials. Issue 5 (26th April 2012) - Kesavan, K.; Ravisankar, K.; Senthil, R.; Arun Sundaram, B.; Parivallal, S.
<x xml:space="preserve">Abstract</x> Fiber Bragg grating (FBG) sensors are the most recent type of fiber optic sensors, which are gaining importance in the field of structural health monitoring of civil infrastructure. These are proven to be more versatile due to their distinct advantages such as high sensitivity, immunity to electromagnetic interference, ease of multiplexing, and remote sensing. These are suitable for the long‐term monitoring of the structures. The FBG sensors are found to be very effective in strain and temperature sensing. However, the FBG sensors are not self‐temperature compensated and the total strain obtained using FBG sensor is the sum of the strain induced due to mechanical load and the apparent strain induced due to temperature. In this article a method to calibrate the apparent strain is discussed. A study is carried out on various structural materials such as mild steel, aluminium, concrete, and carbon fiber‐reinforced plastic (CFRP) using bonded and unbounded FBG sensors. This article presents the result in the form of a temperature calibration curve, which can be used to find the actual mechanical strain.